Registration of Hard Red Spring Wheat Germplasm PT771. Issue 2 (31st March 2014) - Spaner, Dean; Navabi, Alireza; Strenzke, Klaus; Asif, Muhammad; Brule-Babel, Anita
Abstract : PT771 (Reg. No. GP‐967, PI 669478) is a Canadian Western Red Spring (CWRS) wheat ( Triticum aestivum L.) line with very good resistance to Fusarium head blight (FHB) or scab [caused by Fusarium graminearum Schwabe; teleomorph Gibberella zeae (Schwein.) Petch] originating from Ning 8331. Developed at University of Alberta using a modified bulk breeding procedure, PT771 derives from the three‐way cross of 'Lovitt'//Ning 8331/'BiggarBSR'/3/'5602HR' made in 2005. PT771 is also resistant to stem rust (caused by Puccinia graminis Pers.:Pers. f. sp. tritici Eriks. & E. Henn.) and stripe rust (caused by P. striiformis Westend.) and expresses a moderately susceptible reaction to leaf rust (caused by Puccinia triticina Eriks.) and an intermediate response to bunt (caused by Tilletia indica Mitra) and loose smut [caused by Ustilago tritici (Pers.) Rostr.]. It is released because it has a high level of resistance to FHB combined with good agronomic and end‐use quality of the CWRS wheat class.